Penciptaan Nilai Ekonomi Bagi Anggota: Analisis Faktor Partisipasi Dan Manfaat Tidak Langsung melalui Pendekatan Economic Value Added (EVA) - Rima Elya Dasuki; Euis Siti Nurpalihah (J-Coop : Journal of Co-operative, 2026)
Cooperatives, as family-based entities, have a fundamental goal of creating economic well-being for their members. This goal is reflected not only in direct economic benefits in the form of Net Operating Surplus (SHU), but also in indirect economic benefits that are long-term and strategic. This study aims to analyze the factors that influence member participation in cooperative decision-making and business activities, and to measure the contribution of these indirect economic benefits to the creation of economic value for members. This study uses the Economic Value Added (EVA) approach as a quantitative measurement tool to capture the economic value added generated by cooperatives for their members beyond the distribution of SHU. The research method used is a case study with quantitative and qualitative approaches at the West Java Provincial Government Employees Cooperative in Bandung City. Data were collected through questionnaires to measure member participation and financial report documentation studies for EVA calculations. The analysis results show that member participation factors, especially in monitoring and utilization of services, have a significant relationship with member perceptions of indirect economic benefits. The EVA calculation reveals that the cooperative has succeeded in creating positive economic value for its members, where this value represents indirect benefits in the form of increased access, security, and economic stability obtained by members. This study concludes that active member participation is a catalyst in maximizing the economic value added created by cooperatives, thereby strengthening the sustainability and relevance of cooperatives as pillars of a member-based economy.